Development of mobile learning animation media to accelerate Arabic understanding of 1st grade elementary school students - Reno Wulan; Cucu Atikah; Suhendar Suhendar (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2022)
Arabic is one of the world's languages. Seeing this, the ability to speak Arabic is something that absolutely must be mastered in addition to other skills. But for students in grade 1 SD, learning Arabic is an obstacle because of their limitations in writing and reading. The purpose of this study was to determine the feasibility of mobile learning animation media to accelerate the understanding of Arabic in grade 1 elementary school. The research method used in this study is the research and development (R&D) method with the ADDIE development model developed by William Lee. The results of this study indicate that mobile learning animation media is very valid to be used as a learning medium, according to the results of the validation test conducted by material experts by 94% and the validation test of media experts 88%. The conclusion of this research is that mobile learning animation media in Arabic subjects is very feasible to accelerate the understanding of 1st grade elementary school students.